2005
DOI: 10.1038/oby.2005.229
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol: Efficacy and Mechanism of Action of an Anti‐Obesity Agent

Abstract: Obesity is at the forefront of global health issues and directly contributes to many chronic illnesses. Several dietary components show promise in the treatment of obesity, one of which is oil rich in diacylglycerols (DAGs). Present objectives are to examine scientific knowledge concerning DAG to assess evidence supporting the effects on substrate oxidation rates, body weight and fat mass, and blood lipids, and to assess safety, as well as elucidate potential mechanisms of action. DAG can be synthesized by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
66
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 44 publications
0
66
3
1
Order By: Relevance
“…Our DAG and TAG oil challenges were performed on the background of 5 weeks of each diet (DAG-or TAG-enriched NCEP diets). Finally, the longterm, chronic background diets of the subjects studied by Takase et al (35) were likely different from those of our subjects: in Western populations, the consumption of fats and oils accounts for at least 30% of total calories in the diet (23), whereas in Japan, the estimated percentage of fat calories is between 19.5% and 24% (50).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our DAG and TAG oil challenges were performed on the background of 5 weeks of each diet (DAG-or TAG-enriched NCEP diets). Finally, the longterm, chronic background diets of the subjects studied by Takase et al (35) were likely different from those of our subjects: in Western populations, the consumption of fats and oils accounts for at least 30% of total calories in the diet (23), whereas in Japan, the estimated percentage of fat calories is between 19.5% and 24% (50).…”
Section: Discussionmentioning
confidence: 88%
“…Recent interest relevant to this issue has focused on 1,3-DAG oil as such a diet alternative. This interest derives from the hypothesis that 1,3-DAG and 1-DAG are poor substrates for the reesterification of diet-derived FA in the enterocyte (23). Thus, after ingesting a DAG-enriched meal, less diet-derived FA would be incorporated into chylomicron TG, reducing the PP entry of dietary TG into the circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Recent studies have reported that DAG oil has nutritional properties that are distinct from those of TAG oil because of differences in chemical structure. 11 Human studies in the US and Japan have demonstrated that long-term consumption of a diet containing DAG oil enhances loss of body weight and BF compared with a TAG oil with a similar fatty acid composition. 12,13 Animal studies have shown that both b-oxidation and expression of lipid metabolism-related genes in the liver and small intestine are enhanced with chronic DAG oil ingestion compared with TAG oil ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…Although alimentotherapy, exercise, and habit amendment should all be part of the routine method to suppress obesity, there have also been some real advances in the development of chemically synthesized drugs to treat obesity [13]. These drugs can be largely divided into two categories; one class of drugs reduces food intake by suppressing appetite, and the other stimulates fat metabolism, suppresses lipogenesis, and increases metabolic activity [14].…”
Section: Introductionmentioning
confidence: 99%